Day 3 Thu, August 13, 2015 2015
DOI: 10.2118/174653-ms
|View full text |Cite
|
Sign up to set email alerts
|

An Innovative Approach to Make HPAM an Effective Solution to Optimize the Low Salinity ASP Application in Caracara Sur Field, Colombia - Field Case

Abstract: To ensure a technically and economically viable chemical Enhanced Oil Recovery (cEOR) project in the Caracara Sur Field (Llanos Basin Colombia), several challenges were faced. One of the challenges described in a previous work (Cubillos et al. 2013), is the design of an efficient chemical formulation stable at reservoir conditions. Comprehensive laboratory work has been undertaken, resulting in an Alcali Surfactant Polymer (ASP) formulation containing hydrolysed polyacrylamide (HPAM) as a mobility control agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The selection of polymer for the current field case has been explained elsewhere (Cubillos 2015). The authors found that hydrolyzed polyacrylamide was valid for this reservoir even though the high reservoir temperature (86°C).…”
Section: Polymer Selectionmentioning
confidence: 94%
See 1 more Smart Citation
“…The selection of polymer for the current field case has been explained elsewhere (Cubillos 2015). The authors found that hydrolyzed polyacrylamide was valid for this reservoir even though the high reservoir temperature (86°C).…”
Section: Polymer Selectionmentioning
confidence: 94%
“…During the selection of the most suitable polymer (Cubillos 2015), the long-term thermal stability of different polymers in alkali-polymer solutions in production water was assessed according to the API RP 63 standard. The same approach is followed for the assessment of thermal stability of ASP solutions.…”
Section: Long-term Thermal Stabilitymentioning
confidence: 99%